Comparison of two methodologies on spectrum sharing information for unlicensed use in the 6‐GHz band. Issue 4 (8th December 2021) - Um, Jungsun; Kim, Bongsu; Kim, Igor; Park, Seungkeun
Abstract: With the increasing demand for unlicensed spectrum, several regulators have been opening up the 6‐GHz band for unlicensed use while ensuring compliance with the technical requirement to avoid harmful interference in the existing primary services (PSs). In this paper, we present two methodologies, a channel‐based method and a frequency‐based method, which are applicable to a frequency coordination system that calculates the permissible transmit power in the channels or frequencies available to a secondary service (SS). In addition, we have demonstrated that the available transmit power of an SS can be maximized by adjusting the power allocation of the assigned resource units under the condition that the channel of the SS is partially overlapped with that of the PS. Based on the analysis results, it is suggested that it would be better to utilize the two methods selectively according to the operating channel conditions of the PS and the SS.